PERAN GURU BK DAN PAI DALAM MENGATASI PROBLEMATIKA TERHADAP TREND MEDIA SOSIAL REMAJA SMP SHAILENDRA PELEMBANG - Marlia, Ani; Darmawan, M. Ilham; Triana Sari, Indah; Rendrahadi, Dwi; Nosa, Athya; Agustina, Amalia; Kusmara, Patsy Wida (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
This article discusses the important role of Counseling Guidance (BK) and Islamic Religious Education (PAI) teachers in dealing with problems arising from social media trends among teenagers. This study uses interview and observation methods to explore the opinions and strategies that have been used by BK and PAI teachers in dealing with issues that arise due to the use of social media. The findings show that collaboration between the two teachers provides a holistic approach in solving problems, starting from managing stress, understanding the impact of online behavior, to strengthening spiritual values. The results of this research provide an illustration of the need for an active and collaborative role from BK and PAI teachers in creating a healthy and supportive learning environment amidst the influence of social media. This article also underlines the importance of integrating psychological approaches and religious values in efforts to prevent and handle problems arising from social media trends among teenagers. It is hoped that this article can provide guidance and inspiration for other educational institutions in facing similar challenges.